Supersymmetric AdS solitons and the interconnection of different vacua of N = 4 Super Yang-Mills - Anabalón, Andrés [UNESP]; Nastase, Horatiu [UNESP]; Oyarzo, Marcelo (Springer Nature, 2024)
We find AdS soliton solutions in 5-dimensional gauged supergravity, obtained from the S5 compactification of type IIB, with a dilaton saturating the Breitenlohner-Freedman bound. The solutions depend on the value of the periodicity of an S1 cycle and the boundary values for two U(1) gauge fields, and give a scalar VEV in the dual field theory. At certain values of the gauge sources we have supersymmetric solutions, corresponding to supersymmetric flows, which are a deformation of the Coulomb Branch flow in N = 4 SYM. The solutions parameterize quantum phase transitions between a discrete spectrum phase, a continuous above a mass gap phase, and a continuous without a mass gap phase, in 2+1 dimensions. We analyze the phase diagram in terms of the QFT sources and we find that for every value for them, there are always two branches of supergravity solutions. We find that these two branches of solitons correspond to two possible vacua existing in the dual QFT when fermions are anti-periodic on an S1. We describe the interconnection of these states in the QFT at strong ’t Hooft coupling in the large N limit. In 10 dimensions, our solutions are related to deformations of D3-brane distributions.
Keywords: AdS-CFT Correspondence; Gauge-Gravity Correspondence